Islamic Values and Work Ethics on Entrepreneural Performance and its Effects on Intention to Growing Business - Kaukab, M. Elfan; Adawiyah, Wiwiek Rabiatul; Hayati, Sri (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to investigate the effects of Islamic values and Islamic work ethics on performance and its effect on intention to growing business. For this purpose, the research was carried out on 54 entrepreneurs from Nahdliyin Entrepreneurs Association, Indonesia. Multiple regression and correlation is used to test research hypotheses. According to research findings, it was found that Islamic values and work ethics had positive effect on entrepreneurial performance whereas business performace affected growth intention. When we analyzed the effects of Islamic values and Islamic work ethics on intention to growing business, it was found that performance has partial mediatory role for the relationship between Islamic work ethics and growth intention. Islamic values and and Islamic work ethics allows the employee to work safely, ethically, and positively. Through the entrepreneurial performance, the growth intention of the entrepreneur increase.